Rancang Bangun Frame Konstruksi Modifikasi Mesin 3D Printer Untuk Memperluas Area Kerja Pengerjaan - Muhammad Naufal Rafi; Budianto Budianto; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
In the execution of Rapid Prototyping or modeling, almost all industries or companies rely on the usefulness of this 3D Printer machine. Of course, by making a prototype model case that has large dimensions, widths or volumes, the new engine users can redistribute the modeling images to bedivided into several parts or segments. This is done using an assembly technique with several prototype models that have been made, the time needed is long enough to redraw and print part models that will be assembled as we want. With these problems, the design and modification of frame construction are needed in accordance with the expansion of the work area on the axis of the 3D Printer FDM technology. It is expected that with the expansion of this area, the world of industry or manufacturing is able to apply its ideas in real and direct ways by utilizing 3D printing machines. The results of the design of this 3D printer machine are that it can move mechanically the x axis by 680 mm, the y axis by 565 mm, and the z axis by 635mm. This machine has a performance with a print area of the x-axis x 300 mm, y axis 300 mm and z axis 350 mm with the precision of the print specimen 0.1 mm - 0.2 mm.